Biomechanical properties following open wedge high tibial osteotomy: Plate fixator combined with dynamic locking screws versus standard locking screws. (December 2018) - Schröter, Steffen; Hoffmann, Tobias; Döbele, Stefan; Welke, Bastian; Hurschler, Christof; Schwarze, Michael; Stöckle, Ulrich; Freude, Thomas; Ateschrang, Atesch
Abstract: Background: Open wedge high tibial osteotomy is widespread in treating osteoarthritis of the knee. Bone healing of the gap and the necessity of bone substitutes are under discussion. Increasing movement of the osteotomy gap can improve bone healing, while excessive movement should be avoided. It was hypothesised that the use of dynamic locking screws, compared to standard locking screws, will increase interfragmental motion while construct stability persists. Methods: In 20 tibia sawbones open wedge high tibial osteotomy was performed using standard locking screws or dynamic locking screws. An incremental cyclic (2 Hz) compression to termination protocol was applied using a material testing machine (MTS MiniBionix 858). Relative motion of the osteotomy and construct stability were measured using an optical tracking system (PONTOS 5M system). Levels of significance were set to 0.05. Findings: 19 Sawbones were statistically evaluated. Interfragmental motion increased significantly with dynamic locking screws compared to standard locking screws (P < 0.001). Lateral hinge fractured after a mean of 29, 489 (dynamic locking screws) vs. 48, 111 (standard locking screws) load cycles at a median load level 3 (50–1120 N) in dynamic locking screws group and at a median load level 5 (50–1440 N) (P = 0.002) in standard locking screws group. Interpretation: Using dynamic locking screws in open wedge high tibial osteotomy increases interfragmental motion within the range of optimal bone healing. A decrease in construct stability has to be considered compared to standard locking screws. Highlights: Interfragmental motion is increased using dynamic locking screws. Osteotomy movement within the range of optimal bone healing can be expected. Reduced construct stability has to be considered. Lateral hinge fracture occurs earlier compared to standard locking screws.